Genome-Wide Characterization of the Aquaporin Gene Family in Radish and Functional Analysis of RsPIP2-6 Involved in Salt Stress - Yi, Xiaofang; Sun, Xiaochuan; Tian, Rong; Li, Kexin; Ni, Meng; Ying, Jiali; Xu, Liang; Liu, Liwang; Wang, Yan (Frontiers in Plant Science, 2022)
Aquaporins (AQPs) constitute a highly diverse family of channel proteins that transport water and neutral solutes. The AQPs play crucial roles in plant development and stress responses. However, the characterization and biological functions of RsAQPs in radish (Raphanus sativus L.) are still elusive at present. In this study, 61 non-redundant members of aquaporin encoding genes were identified from radish genome database, which were located on the nine chromosomes. Radish AQPs (RsAQPs) were divided into four subfamilies including 21 plasma membrane intrinsic proteins (PIPs), 19 tonoplast intrinsic proteins (TIPs), 16 NOD-like intrinsic proteins (NIPs) and five small basic intrinsic proteins (SIPs) through phylogenetic analysis. All of the RsAQPs members contained highly conserved motifs (Motifs 1 and 4) and transmembrane regions, indicating that potential transmembrane transport function of RsAQPs. Tissue and stage specific expression patterns of aquaporin genes analysis based on RNA-seq data revealed the expression levels of PIPs were generally higher than TIPs, NIPs and SIPs in radish. In addition, quantitative real-time polymerase chain reaction (qRT-PCR) revealed that seven selected RsPIPs according to our previous transcriptome data (e.g. RsPIP1-3, 1-6, 2-1, 2-6, 2-10, 2-13 and 2-14) exhibited significant up-regulation in roots of salt-tolerant radish genotype. Especially, the transcriptional levels of RsPIP2-6 were dramatically increased at 6 h of 150 mM NaCl treatment during taproot thickening stage. Additionally, over-expression of RsPIP2-6 could enhance the salt tolerance by Agrobacterium rhizogenes-mediated transgenic radish hairy roots, which exhibited the mitigatory effects of plants growth reduction, drop in leaf relative water content (RWC) and the alleviation amount of O2− in cells by nitro blue tetrazolium (NBT) staining under salt stress. These findings are helpful for deeply dissecting the biological function mechanism of RsAQPs on salt stress response, facilitating practical application and genetic improvement of abiotic stress resistance in radish.